Dense captioning and multidimensional evaluations for indoor robotic scenes - Wang, Hua; Wang, Wenshuai; Li, Wenhao; Liu, Hong (Frontiers in Neurorobotics, 2023)
The field of human-computer interaction is expanding, especially within the domain of intelligent technologies. Scene understanding, which entails the generation of advanced semantic descriptions from scene content, is crucial for effective interaction. Despite its importance, it remains a significant challenge. This study introduces RGBD2Cap, an innovative method that uses RGBD images for scene semantic description. We utilize a multimodal fusion module to integrate RGB and Depth information for extracting multi-level features. And the method also incorporates target detection and region proposal network and a top-down attention LSTM network to generate semantic descriptions. The experimental data are derived from the ScanRefer indoor scene dataset, with RGB and depth images rendered from ScanNet's 3D scene serving as the model's input. The method outperforms the DenseCap network in several metrics, including BLEU, CIDEr, and METEOR. Ablation studies have confirmed the essential role of the RGBD fusion module in the method's success. Furthermore, the practical applicability of our method was verified within the AI2-THOR embodied intelligence experimental environment, showcasing its reliability.